Politické myšlení Alberta Camuse v kontextu motivu lidské přirozenosti - Michal Müller (Svět Literatury, 2020)
This article points to the interdisciplinary overlap of literary and journalistic work by Albert Camus and political philosophy. Unfortunately, political thoughts that represent a significant aspect of his work are often overshadowed by the exaggerated appeal of many interprets and literary critics to the philosophy of absurdity and its existential dimension. The article proposes the interpretative framework of human nature as a unifying element between the concepts of absurd and revolt, and uses it to assess Camus’s moderate political position. The article concludes that Camus’s works can be useful in considering the necessary conditions for political discussion and interpersonal dialogue, and in highlighting the importance of literature within this dialogue.